If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 3o) + 9o = 0 Reorder the terms: (3o + 5x) + 9o = 0 Remove parenthesis around (3o + 5x) 3o + 5x + 9o = 0 Reorder the terms: 3o + 9o + 5x = 0 Combine like terms: 3o + 9o = 12o 12o + 5x = 0 Solving 12o + 5x = 0 Solving for variable 'o'. Move all terms containing o to the left, all other terms to the right. Add '-5x' to each side of the equation. 12o + 5x + -5x = 0 + -5x Combine like terms: 5x + -5x = 0 12o + 0 = 0 + -5x 12o = 0 + -5x Remove the zero: 12o = -5x Divide each side by '12'. o = -0.4166666667x Simplifying o = -0.4166666667x
| -3(4)+-2=x | | -(x-1)-4(x-3)=58 | | -0.2(-15x-10)=10 | | -7(4)+15=x | | z(2z-9)(z+4)=0 | | x^2+kx-9=0 | | 5=4(x-4)+3-3x | | 30+y=3y | | 12x+4+13x-4=180 | | (m-1)x^2+mx+2m=0 | | n+(n+1)+(n+2)+(n+3)=1368 | | 30+y=6y | | 6x+8-5x=14-15x-16 | | 6x/5+12x=3(5/2) | | 3b^2+20b+31=6 | | x^4+10x^3-59x^2+40x+60=0 | | 12y-8=-4 | | 34x-543=321 | | 2x-34=87 | | 29x^2+10x-21=0 | | 3=3(x-2)+5-2x | | (14y+11)+(-4y-3)= | | 15=5(x+9) | | 13p+16q+p-5q-7p= | | 2x(4x-1)=7 | | (14y+11)+(14y-3)= | | 5-9x=35-23x | | D=Bgx | | 0.8x+6.7=2.3 | | -6x+19+8x+19=-6 | | 10(x+2)=2(x+10) | | (2x-1)(x^2+4x-4)= |